Potential of Small and Medium Enterprises Growth: Role of Internal and External Factors of Commercial Banks’ Credit Accessibility - Odumesi, Abolaji Oladimeji; Olubiyi, Timilehin Olasoji; Kowo, Solomon Akpoviroro; Abosi, Ezinne; Azzahra, Adelia; Savandha, Septien Dwi (Asian Journal of Social and Humanities, 2024)
The common factors determining Commercial banks’ lending to SMEs are internal and external. This study assessed the combined effect of these two factors that determine the commercial banks’ credit accessibility and SMEs’ growth in Nigeria. Data from 1990 to 2023 were used to evaluate the hypothesis. The outcome demonstrates that the internal factors of commercial banks factors on credit accessibility to SMEs were 0.039110 and statistically significant at the 5% level (p-value = 0.0254). The outcome suggests that internal factors of commercial bank determinants on the availability of credit to SMEs play a significant impact on the expansion of SMEs in Nigeria. At the 5 per cent level, the external influence of commercial banks on SMEs' access to credit was -0.014003 and statistically insignificant (p-value = 0.2757). The results will substantially aid in designing and implementing monetary policy about the cash reserve requirement. It also conveys to SMEs the significance of cash reserve requirements in improving loan accessibility in Nigeria. As a result, the paper recommends that monetary policy be continually improved to favour SMEs because doing so will facilitate their expansion.